Convergence of LR algorithm for a one-point spectrum tridiagonal matrix - Ferreira, Carla (2009)
We proved convergence for the basic LR algorithm on a real unreduced tridiagonal matrix with a one-point spectrum - the Jordan form is one big Jordan block. First we develop properties of eigenvector matrices. We also show how to deal with the singular case.